Pituitary and brain dopamine D2 receptors regulate liver gene sexual dimorphism - Ramirez, Maria Cecilia (2015)
Liver sexual gene dimorphism, which depends mainly on specific patterns of GH secretion, may underlie differential susceptibility to some liver diseases. Because GH and prolactin secretion are regulated by dopaminergic pathways, we studied the participation of brain and lactotrope dopamine 2 receptors (D2Rs) on liver gene sexual dimorphism, to explore a link between the brain and liver gene expression. We used global D2R knockout mice (Drd2(-/-)) and conducted a functional dissection strategy based on cell-specific Drd2 inactivation in neurons (neuroDrd2KO) or pituitary lactotropes. Disruption of neuronal D2Rs (which impaired the GH axis) decreased most of male or female-predominant class I liver genes and increased female-predominant class II genes in males, consistent with the positive (class I) or negative (class II) regulation of these genes by GH. Notably, sexual dimorphism was lost for class I and II genes in neuroDrd2KO mice. Disruption of lactotrope D2Rs did not modify class I or II genes in either sex, because GH axis was preserved. But surprisingly, 1 class II gene (Prlr) and female-predominant class I genes were markedly up-regulated in lacDrd2KO females, pointing to direct or indirect effects of prolactin in the regulation of selected female-predominant liver genes. This suggestion was strengthened in the hyperprolactinemic Drd2(-/-) female mouse, in which increased expression of the same 4 liver genes was observed, despite a decreased GH axis. We hereby demonstrate endocrine-mediated D2R actions on sexual dimorphic liver gene expression, which may be relevant during chronic dopaminergic medications in psychiatric disease.